2021
DOI: 10.3329/bjms.v20i4.54146
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in relation to clinical, endocrine and metabolic parameters in infertile women with polycystic ovary syndrome: the South Asian perspective

Abstract: Background: Polycystic ovary syndrome (PCOS) affects 5-10% of reproductive age women and it is a common cause of infertility in young women. Most of the infertile women with PCOS are overweight or obese. Obesity or excess fat aggravates the endocrine and metabolic dysfunction in women with PCOS. Weight management is the first line measure advised to infertile PCOS women who are overweight or obese. The objective of the study was to explore the association of obesity with the clinical, endocrine and metabolic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…A study stated that obesity is related to hyperandrogenism, hyperinsulinemia, insulin resistance, and metabolic syndrome in infertile women. 21 This study found that the majority of UDT husbands were between the ages of 20 and 30, with a mean age of 28 years for unilateral and 29 years for bilateral procedures. Age at diagnosis is an important prognostic factor for undescended testes because the risk of developing testicular cancer and infertility rises with age.…”
Section: Characteristics Of Udt Husbandsmentioning
confidence: 68%
“…A study stated that obesity is related to hyperandrogenism, hyperinsulinemia, insulin resistance, and metabolic syndrome in infertile women. 21 This study found that the majority of UDT husbands were between the ages of 20 and 30, with a mean age of 28 years for unilateral and 29 years for bilateral procedures. Age at diagnosis is an important prognostic factor for undescended testes because the risk of developing testicular cancer and infertility rises with age.…”
Section: Characteristics Of Udt Husbandsmentioning
confidence: 68%
“…10 Excess body fat deposition resulting in overweight and obesity causes many adverse effects on human health. 37 Overweight and obesity aggravates the endocrine and metabolic dysfunction, 38 decreases the flexibility and fitness of cardio-pulmonary and musculoskeletal functions. 39 Worldwide in the last 40 years, the overweight and obesity has increased significantly.…”
Section: Table-1: Sociodemographic Characteristics Of the Participant...mentioning
confidence: 99%
“…Figure(5) shows an observous raise in the level of the prolactin hormone in patients with PCOS (683.26 ± 236.06 ng / ml) compared to healthy women (208.69 ± 67.06 ng / ml).…”
mentioning
confidence: 93%
“…In addition to polycystic ovaries, infertility and obesity, this disorder is characterized by excessive hairiness, which is called hirsutism [4] . In this disorder, the outer layer of the ovary holds together, preventing the mature egg from emerging the ovarian layer, and without the release of this egg, the pregnancy process does not occur [5] . In addition, there will be an enlargement in the size of the ovary, which may reach three times its size, as well as an increase in the concentration of ovarian tissue in the middle of the ovary around the cysts.…”
Section: Introductionmentioning
confidence: 99%